Social security in the CARICOM Single Market & Economy : a current assessment and a road map for achieving future financial sustainability and income security - Osborne, Derek (CCS GeorgetownGY, 2004)
Examines the state of social security systems in Member States and Associate Members of the Community. Reviews the rules that govern each scheme as well as historical and projected financial and demographic trends. Makes policy recommendations which would guarantee the continuation of the social protection systems, of the CARICOM Single Market & Economy.